The Role of Habitat Amount and Vegetation Density for Explaining Loss of Small-Mammal Diversity in a South American Woodland Savanna - Melo, Geruza L.; Cerezer, Felipe O.; Sponchiado, Jonas; Cáceres, Nilton C. (Frontiers in Ecology and Evolution, 2022)
The focus of research and conservation in tropical regions is mainly devoted to forest ecosystems, usually neglecting the processes underlying widespread, more open biomes, like savannas. Here we test a wide range of sampled woodland sites across the South American savanna for the direct and indirect effects of habitat loss and vegetation density on the diversity of small-mammal species. We quantify the direction and magnitude of the effects of habitat amount (habitat loss), vegetation density (tree or foliage density), and patch size (species-area effect) on species composition and richness. We also test whether the relative effect sizes of landscape and patch-related metrics predict a persistence gradient from habitat specialist to generalist species across 54 sites. We used structural equation models (SEM) to test our predictions. After 22,032 trap-nights considering all sampled sites and 20 small-mammal species identified, the structural equation model explained 23.5% of the variance in the richness of small-mammal species. Overall, we found that landscape-level metrics were more important in explaining species richness, with a secondary role of patch-level metrics such as vegetation density. The direct effect of local landscape was significant for explaining species richness variation, but a strong positive association between regional and local landscapes was also present. Furthermore, considering the direct and indirect paths, SEM explained 46.2% of the species composition gradient. In contrast to species richness, we recorded that the combined landscape-level and patch-level metrics are crucial to determining small-mammal species composition at savanna patches. The small mammals from the South American woodland savanna exhibit clear ecological gradients on their species composition and richness, driven by habitat specialist (e.g., Thrichomys fosteri, Monodelphis domestica, and Thylamys macrurus) and generalist (e.g., Didelphis albiventris, Rhipidomys macrurus, and Calomys callosus) species’ responses to habitat amount and/or vegetation density, as seen in dense-forest Neotropical biomes.